Female farmers facing food insecurity and climate change vulnerability in rural area - Palupi Lindiasari Samputra (Progress in Disaster Science)
Frequent lousy weather impacts the prevalence of food insecurity among women farmers and makes the agricultural sector more vulnerable to climate change. Detection of food insecurity due to climate change vulnerability using a quantitative survey method of 150 female farming households in Sleman. Based on data analysis using the FIES questionnaire and multinominal regression, 63 % of female farmers reported experiencing food insecurity, 24 % reported experiencing mild food insecurity, and the remaining 13 % reported experiencing moderate food insecurity. The frequent exposure to drought in agriculture experienced by women farmers and their ability to respond to the impacts of climate change influence the risk of food insecurity. Women farmers must have the right human, social, financial, and physical resources to adapt. Due to repeated exposure to drought, advanced age, farmers burdened with land rental costs, and lack of participation in farmers' associations tend to experience moderate food insecurity. Other contributing factors are greater remittance dependence and meager agricultural income (< IDR 500 thousand per month). On the other hand, if they can earn a monthly salary of IDR 2 million, own a house, and complete at least primary education, their chances of achieving food security will increase significantly.